Quantifying day-to-day variability of O/N2 and its correlation with geomagnetic activity using GOLD - Martinez, Benjamin C.; Lu, Xian (Frontiers in Astronomy and Space Sciences, 2023)
We quantify the short-term (<30 day) variability of column O/N2 measured by GOLD from January 2019 to August 2022 for various geomagnetic activity conditions. We find enhanced variabilities at high latitudes during active (Kp 3.0) times and weak but statistically significant variabilities at low latitudes. For active times, the largest absolute variability of O/N2 ratio is 0.14 and the largest relative variability is 20.6% at ~60.0°N in Fall, which are about twice those of quiet times. The variability at higher latitudes can be larger than that of lower latitudes by a factor of 5-8. We further quantify contributions of magnetospheric forcing to O/N2 variability in the Ionosphere-Thermosphere region by correlating O/N2 perturbations with Dst. During geomagnetic active times, positive correlations as large as +0.66 and negative correlations as large as –0.65 are found at high and low latitudes, respectively, indicative of storm-induced O/N2 upwelling and downwelling. During quiet times, correlations between O/N2 perturbations and Dst become insignificant at all latitudes, implying a more substantial contribution from below. O/N2 variabilities maximize in Fall and decrease towards Summer, while correlations maximize in Spring/Summer and decrease in Winter/Spring, which may be related to seasonal variations of geomagnetic activity and mean circulation.